POLIGAMI DAN MONOGAMI DALAM ISLAM: PERUBAHAN PARADIGMA PERNIKAHAN - Mahendra Putra, Eka (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This study examines the transformation of Islamic marriage from polygamy to monogamy by analyzing its social, theological, and moral dimensions. The central issue lies in the tension between the Qur’anic allowance of polygamy and modern ideals of justice and gender equality. Using a qualitative-descriptive approach through library research, this study focuses on KH. Husein Muhammad’s interpretation of Islamic family law and employs a contextual hermeneutic method. Findings reveal that polygamy functions as a contextual dispensation (rukhṣah) rather than a universal norm, its relevance diminishing in the modern era due to the challenge of ensuring true justice. Monogamy, in contrast, aligns more closely with the maqāṣid al-sharī‘ah principles of fairness, compassion, and harmony, positioning it as the ideal model for contemporary Muslim marriages.